Тhermal and environmental characteristics of glass produced from metalurgical wastes - E. Ljatifi, A. Kamusheva, G. Načevski, E. Karamanova, A. Petrovski, A. Karamanov, P. Paunović (Montenegrin Society for Corrosion, Materials and Environment Protection and Faculty of Metallurgy and Technology, University of Montenegro, 2015)
The subject of this study is glass produced by mixed metallurgical waste from ferronickel production, aimed for further production of glass-ceramic. Characterization of waste materials includes determination of chemical and mineralogical composition and standard leaching test. The waste materials contain several heavy metals (Fe, Ni, Mn, Zn, Cr) which exceed the applied limits and can be potential hazard to the soils. On the other hand, the waste mixture contains sufficient amount of glass-forming component - SiO2. The components in the waste mixture aimed for glass production were in the ratio as they are produced in the Fe-Ni smelter (flay ash:electro-furnace slag:converter slag = 1:10:1). Thermal characterization of the glass was performed by means of hot stage microscopy (HSM) and DTA analysis, where the temperatures of sintering, softening, smelting and crystallization were determined. The results highlight that fine-crystalline glass-ceramic with high crystallinity can be obtained. Standard leaching test has shown that the concentration of all heavy metals is bellow applied limits for 5 to 400 times. Thus, the produced glass is environmental safety product.